Mix and measure II: joint high-energy laboratory powder diffraction and microtomography for cement hydration studies - Fernández-Sánchez, Jaime; Cuesta, Ana; Shirani, Shiva; Redondo-Soto, Cinthya; Torre, Ángeles G. de la; Santacruz-Cruz, María Isabel; Salcedo, Inés R.; León-Reina, Laura; García-Aranda, Miguel Ángel (Wiley, 2024)
Portland cements (PCs) and cement blends are multiphase materials of different fineness, and quantitatively analysing their hydration pathways is very chal- lenging. The dissolution (hydration) of the initial crystalline and amorphous phases must be determined, as well as the formation of labile (such as ettringite), reactive (such as portlandite) and amorphous (such as calcium silicate hydrate gel) components. The microstructural changes with hydration time must also be mapped out. To address this robustly and accurately, an innovative approach is being developed based on in situ measurements of pastes without any sample conditioning. Data are sequentially acquired by Mo K1 laboratory X-ray powder diffraction (LXRPD) and microtomography (mCT), where the same volume is scanned with time to reduce variability. Wide capillaries (2 mm in diameter) are key to avoid artefacts, e.g. self-desiccation, and to have excellent particle averaging. This methodology is tested in three cement paste samples: (i) a commercial PC 52.5 R, (ii) a blend of 80 wt% of this PC and 20 wt% quartz, to simulate an addition of supplementary cementitious materials, and (iii) a blend of 80 wt% PC and 20 wt% limestone, to simulate a limestone Portland cement. LXRPD data are acquired at 3 h and 1, 3, 7 and 28 days, and mCT data are collected at 12 h and 1, 3, 7 and 28 days. Later age data can also be easily acquired. In this methodology, the amounts of the crystalline phases are directly obtained from Rietveld analysis and the amorphous phase contents are obtained from mass-balance calculations. From the mCT study, and within the attained spatial resolution, three components (porosity, hydrated products and unhy- drated cement particles) are determined. The analyses quantitatively demon- strate the filler effect of quartz and limestone in the hydration of alite and the calcium aluminate phases. Further hydration details are discussed.
Keywords: Cemento Portland -- Análisis; Cementos Portland; Mezclas de cemento; Estudios in situ; Análisis de fase cuantitativa de Rietveld; Imágenes de rayos X; Efecto de relleno